2020
DOI: 10.3390/antibiotics9020039
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Ceftriaxone Versus Multiple Dosing Regimes of Intravenous Anti-Staphylococcal Antibiotics for Methicillin-Susceptible Staphylococcus aureus (MSSA): A Systematic Review

Abstract: Background: Methicillin-susceptible Staphylococcus aureus (MSSA) is a common pathogen associated with a range of clinically important infections. MSSA can cause deep-seated infections requiring prolonged courses of intravenous antibiotic therapy to achieve effective resolution. The move toward ambulatory or outpatient delivery of parenteral antibiotics has led to an increase in the use of ceftriaxone as a pragmatic first choice given its advantageous single daily dosing schedule. Objective: To compare the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The approach of administering empiric antibiotic therapy solely to patients who were admitted for SARS-CoV-2 and who presented with a chest X-ray suggestive of bacterial infection, have a need for direct ICU admission, or are severely immunocompromised should be reconsidered. When bacterial co-infection in SARS-CoV-2 patients is suspected, an antibiotic approach with optimal S. aureus coverage, such as ceftaroline, ceftriaxone, or cefazolin plus levofloxacin, is recommended in areas with methicillin-sensitive S. aureus prevalence [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…The approach of administering empiric antibiotic therapy solely to patients who were admitted for SARS-CoV-2 and who presented with a chest X-ray suggestive of bacterial infection, have a need for direct ICU admission, or are severely immunocompromised should be reconsidered. When bacterial co-infection in SARS-CoV-2 patients is suspected, an antibiotic approach with optimal S. aureus coverage, such as ceftaroline, ceftriaxone, or cefazolin plus levofloxacin, is recommended in areas with methicillin-sensitive S. aureus prevalence [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have conflicting results and limited sample sizes; thus, robust evidence is inconclusive. A recent systematic review and meta-analysis and another systematic review evaluated ceftriaxone use for MSSA infections [11,12]. However, these studies evaluated mixed infections and did not include all of the available studies.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that ceftriaxone has a broad potency spectrum against Gram-positive and Gram-negative bacteria [ 15 ]. In addition, ceftriaxone is used frequently to treat MSSA infections [ 16 , 17 ]. It has been used as a first-line treatment against bacteremia alongside other antibiotic combinations [ 18 ].…”
Section: Discussionmentioning
confidence: 99%